Pengembangan perangkat pembelajaran dengan penemuan terbimbing pada pokok bahasan fungsi kelas VIII (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this research is to produce a mathematical learning tool with guided discovery on the subject of valid and practical functions. The learning tools developed are in the form of a Learning Implementation Plan and Student Worksheet. The development of learning devices in research uses a 4D model which is modified into several stages, namely defining, designing and developing. Data collection instruments in the form of validation sheets, teacher and student activity observation sheets, and student and teacher response questionnaires. The learning tools developed were validated by 2 expert lecturers and 1 mathematics teacher. The learning tools that have been validated and revised were tested in SMP class VIII with a total of 23 students. The results obtained with the level of validity of the learning implementation plan is 83.70 and the validity of the active worksheet is 80.62, which means that learning implementation plan and student worksheet are included in the valid category and can be used with minor revisions, while the practicality of the lesson plan is 87.50 and the practicality of student worksheet is 85.14 from these results. it was found that the learning implementation plan and student worksheet that the researcher developed were categorized as very practical and could be used well.
Keywords: development of lesson plans; student worksheet; guided discovery